„Sokół” wileński opoką polskości i jego spuścizna - Kamilewicz-Rucińska, Danuta (Biuletyn Historii Wychowania, 2024)
The history of the “Sokol” (eng. Falcon) Gymnastic Society in Vilnius covers various periods and political circumstances. The “Falcon’s nest” was founded during Russian captivity and was initially an illegal organization. The Russian authorities kept a close eye on the Society’s activities, and therefore the Board and activists exercised considerable caution. The “Sokol” of Vilnius launched proper gymnastics, sports as well as cultural and educational activities in 1919 after Poland regained independence. It was a time of its successful development. In addition to sports activities, the Vilnius “Sokol” undertook a wide range of cultural and educational activities, such as running a library, a reading room, a choir and an orchestra, organizing patriotic lectures as well as national and family evenings, publishing brochures, magazines and calendars, and taking an active part in celebrating Polish holidays and public festivities. The “Sokol” Gymnastic Society was also a mainstay of Polish identity in Vilnius. To many Poles today, particularly young people, the “Sokol” Gymnastic Society is an integral part of Polish life in Lithuania. After many difficulties with registration and harassment by the independent Lithuanian state, the “Falcon’s nest” worked intensively with youth promoting Polish culture and national identity, as well as falconry. As it was 100 years ago, the organization focuses on the reflection on the much needed harmony between the human body and spirit. The history of Poland and Lithuania, as well as the history of sports in these territories, are alive in falconry.